Fish assemblages cope with ocean acidification in a shallow volcanic CO2 vent benefiting from an adjacent recovery area - Mirasole A.; Signa G.; Gianguzza P.; Bonaviri C.; Mazzola A.; Vizzini S. (Marine Environmental Research, 2020)
Shallow CO2 vents are used to test ecological hypotheses about the effects of ocean acidification (OA). Here, we studied fish assemblages associated with Cymodocea nodosa meadows exposed to high pCO2/low pH conditions at a natural CO2 vent in the Mediterranean Sea. Using underwater visual census, we assessed fish community structure and biodiversity in a low pH site (close to the CO2 vent), a close control site and a far control site, hypothesising a decline in biodiversity and a homogenization of fish assemblages under OA conditions. Our findings revealed that fish diversity did not show a unique spatial pattern, or even significant relationships with pH, but correlated with seagrass leaf canopy. Among-site similarity was found in the abundance of juveniles, contrary to the expected impacts of OA on early life stages. However, pH seems an important driver in structuring fish assemblage in the low pH site, despite its high similarity with the close control site. This unexpected pattern may represent a combined response of fish mobility, enhanced food resources in the acidified site, and a ‘recovery area’ effect of the adjacent control site.